The genus Ophiocara (Teleostei: Butidae) in Japan, with descriptions of two new species - Kobayashi, Hirozumi; Sato, Mao (Ichthyological research, 2024)
A taxonomic review of the genus Ophiocara Gill 1863 in Japan resulted in a revised diagnosis for Ophiocara ophicephalus (Valenciennes in Cuvier and Valenciennes 1837) and descriptions of two new species, Ophiocara gigas and Ophiocara macrostoma , from the Ryukyu Archipelago. The three species are genetically isolated based on the mitochondrial COI region, being distinguished from each other and other congeners by differing combinations of opercular scale morphology, upper jaw length, caudal fin length, and coloration: Ophiocara ophicephalus is characterized by having ctenoid scales on the operculum and distinct silver or white spots on the head, body, and dorsal and caudal fins, and in juveniles the absence of bright markings on the lower part of the caudal fin base; O. gigas by two broad beige bands on the body, black spots scattered on the trunk, and in juveniles the presence of three bright markings on the caudal fin base; and O. macrostoma by a uniformly dark caudal fin, elongated upper jaw in adults (16.0–17.5% of standard length), and in juveniles the presence of two narrow bright bands on the body and three bright markings on the caudal fin base. One of two distinct color patterns, previously thought to represent intraspecific dimorphism of O . ophicephalus , is now considered characteristic of the new species O . gigas . The three species also exhibited distinct habitats, salinity preference, and maximum body length.